2001
DOI: 10.1007/s11663-001-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic model of nickel smelting and direct high-grade nickel matte smelting processes: Part I. Model development and validation

Abstract: A thermodynamic model has been developed to predict the distribution behavior of Ni, Cu, Co, Fe, S, As, Sb, and Bi in the Outokumpu flash-smelting process, the Outokumpu direct high-grade matte smelting process, and the INCO flash-smelting process. In this model, as many as 16 elements (Ni, Cu, Co, Fe, As, Sb, Bi, S, O, Al, Ca, Mg, Si, N, C, and H) are considered, and two nickel sulfide species are used to allow for modeling of sulfur-deficient mattes. The compositions of the matte, slag, and gaseous phases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…[1] The content increasing matte grade, but {Ni} Mt , {Cu} Mt , and {Co} Mt of Fe 3 O 4 in the slag in the four modes was also in agreement decrease with increasing matte grade. This means that the with the predicted values.…”
Section: Matte Gradementioning
confidence: 69%
See 2 more Smart Citations
“…[1] The content increasing matte grade, but {Ni} Mt , {Cu} Mt , and {Co} Mt of Fe 3 O 4 in the slag in the four modes was also in agreement decrease with increasing matte grade. This means that the with the predicted values.…”
Section: Matte Gradementioning
confidence: 69%
“…This means that the with the predicted values. [1] The operation conditions and recovery rate of valuable metals such as nickel, copper, and the compositions of the charges for these test modes were cobalt is lower in the higher-matte-grade range, especially presented in detail. [2] These are necessary for this modeling for cobalt.…”
Section: Matte Gradementioning
confidence: 99%
See 1 more Smart Citation
“…Yet again the base metal solubility in the slag is highly dependent on the type of concentrate fed to a furnace. Some authors state that increasing the temperature reduces base metal solubility in slag [13,20,21], however others claim that it has a reverse effect [22,23]. Work done by Holzheid et al [24] showed that the solubility of cobalt in silicate melts are little dependent on temperature in the 1300 ℃ to 1600 ℃ range, however it was found that nickel solubilities increased significantly with increasing temperature and also increasing pressure.…”
Section: Effect Of Temperature On Cr Solubilitymentioning
confidence: 99%
“…Ultimately, this will increase the levels of base metals partitioning into the slag, however this may be somewhat due to entrapment of sulphide or matte phases [23].…”
Section: Effect Of Oxygen Potential On Cr Solubilitymentioning
confidence: 99%